Non-Formal Education Management for The Residents of The Rejang Lebong Development Institution - Murni Yanto (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
In The Class IIA Correctional Institution Rejang Lebong in giving directions to prisoners, it provides non-formal training administration as a Package C equivalency school. In offering this instructive assistance, good administration is expected to achieve quality instructive goals. Objectives of exploration: (1) implementation of non-formal instruction program at Rejang Lebong Penitentiary, (2) obstacles faced, and efforts to conquer obstacles in Lapas Rejang Lebong. This kind of examination is a subjective exploration of graphics. Procedures vary information based on perceptions, meetings, and documentation. The results showed that the implementation of a non-formal instruction program for prisoners completed by the penitentiary had gone very well, despite the fact that it actually faced many obstacles. Prison helps PKBM